Estimation and Market Valuation of Environmental Liabilities Relating to Superfund Sites - Barth, Mary E.; McNichols, Maureen F. (Journal of Accounting Research, 1994)
Mary E. Barth, Maureen F. McNichols, Estimation and Market Valuation of Environmental Liabilities Relating to Superfund Sites, Journal of Accounting Research, Vol. 32, Studies on Accounting, Financial Disclosures, and the Law (1994), pp. 177-209